Maybe happy ending [compact disc] : original Broadway cast recording - Aronson, Will, 1981- (Ghostlight Records, 2025)
"Get ready to be swept away! Ghostlight Records presents the Original Broadway Cast Recording of Maybe Happy Ending, the musical sensation that's taken Broadway by storm. USA Today calls it "One of The Very Best Scores to Hit Broadway in Years," and you're about to hear why. Dive into the magic with this heartfelt CD, featuring show photos, complete lyrics, and a personal liner note from the legendary Stephen Trask. This is the cast album you've been waiting for. Set in the near future, Maybe Happy Ending is a beautifully offbeat story about two outcasts near the end of their warranty who discover that even robots can be swept off their feet." --www.cvsmidwesttape.ca.